Articulate Storyline Interactive Media for Grade XI Digestive-Excretory Learning via ASSURE (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
Students' low understanding of complex human digestive and excretory system materials shows a gap in the use of technology-based interactive learning media in high school/MA. This study aims to develop and evaluate the validity, practicality, and effectiveness of Articulate Storyline-based interactive media for learning the human digestive and excretory system in grade XI using the ASSURE design model. The research innovation lies in the integration of interactive multimedia technology with the ASSURE systematic learning approach which includes student analysis, goal setting, media-method selection, material utilization, and evaluation-revision. The research and development (R&D) method was applied with the subjects of grade XI high school/MA students. Data was collected through pretests, user response questionnaires, and expert validation. The results showed that the developed media achieved very high validity (> score of 0.80), excellent practicality of teacher and student assessments (81-100%), and significant effectiveness with an average N-Gain of 0.7227 indicating a substantial improvement in learning outcomes. These findings indicate that the Articulate Storyline interactive media with the ASSURE design is effective in improving understanding of complex biology concepts, making a significant contribution to technology-based science learning innovations in Indonesia, and has the potential to be widely applied for a more engaging and effective transformation of biology education.